Hubungan Aktivitas Fisik dengan Kebugaran Fisik (VO2MAX) pada Remaja di SMA Negeri 76 Jakarta - Putri Risqiana, (2022)
Background: The flow of human growth at the adolescent level then becomes a higher level, namely adulthood. However, there is a change in lifestyle in adolescence, where from doing a lot of physical activity to rarely doing physical activity. This will also be one of the causes of the decline in the level of physical fitness of adolescents, as well as having a negative impact on health and having low fitness in the future. Objective: This study was conducted to determine whether there is a relationship between physical activity and physical fitness (VO2Max) for high school adolescents. Methods: the method of this research is to determine the design in the form of a cross-sectional pattern and the sampling design in the form of random sampling. The research subjects were 67 students/teenagers of 76 Jakarta State Senior High School with an age range of 15 - 18 years. The instrument used is the IPAQ-SF and takes a physical fitness test in the form of a Multistage Fitness Test / Beep Test. The data were then grouped and analysed using a statistical test in the form of SPSS. Results: it was found that the results of physical activity data with physical fitness using the Rank - Spearman statistical test obtained physical fitness (P) = 0.008 (less) p = 0.05 and the value (R) = 0.321 means sufficient, so hypothesis 1 is implemented, absolutely has understanding that there is a relationship between physical activity and physical fitness (VO2Max) in adolescents at SMA Negeri 76 Jakarta. Conclusion: the results showed that there was a relationship between physical activity and physical fitness (VO2Max) of adolescents. Keywords: ipaqsf, physical activity, bleep test, VO2Max, adolescents